The Impact of Agribusiness Mudharabah Financing on Community Welfare: Assessing the Moderating Role of Eco-Literacy in the Sustainable Development Goals (SDGs) - Normasyhuri, Khavid; Huda, Ahsanal; Alfredo, Harold Kevin (Universitas KH. Abdul Chalim Mojokerto, 2026)
The primary issue identified is the unequal access to mudharabah financing in the agricultural sector, which impedes farmer empowerment. Additionally, sustainable natural resource management is adversely affected by the public's inadequate comprehension of eco-literacy. The objective of this investigation is to investigate the impact of agribusiness mudharabah financing on community welfare, with an emphasis on the role of eco-literacy as a moderating variable in the pursuit of the SDGs. SmartPLS 4.0 software was employed to analyse data using a quantitative approach. Purposive sampling was employed to gather primary data, which was subsequently analysed using a Likert scale with a total of 350 respondents. The study's results suggest that mudharabah financing has a beneficial effect on community welfare, and this relationship is further bolstered by eco-literacy. The achievement of SDGs such as No Poverty, No Hunger, Reduced Inequality, and Gender Equality is influenced by the more efficient and environmentally favourable management of enterprises by farmers who comprehend sustainability. This research contributes to the comprehension of the ways in which Islamic financing and eco-literacy can facilitate sustainable development. These results establish a foundation for the creation of financing products that are more sustainable and inclusive, as well as practical suggestions for policymakers to enhance ecological literacy among producers.